Developing participation in water management through water consumers’ associations and the “Water workers’ school” - Jabbarova, Ikbol Khujamuratovna (The Lingua Spectrum, 2026)
This article presents a scientific analysis of the development of participatory governance in Uzbekistan’s water management system through Water Consumers’ Associations (WCAs) and the “Water Workers’ School” initiative. The shortcomings of the centralized water management system inherited from the Soviet era and the institutional reforms carried out during the years of independence, including the establishment of WCAs and the regulatory framework governing their activities, are examined in detail. The legal foundations of WCA operations, their role in collective water governance, and the financial, technical, and institutional challenges they face are thoroughly discussed. The practical outcomes of the “Water Workers’ School” project are examined in detail, particularly its impact on changing the attitudes of farm managers, water distributors (mirabs), and WCA staff toward water conservation, the introduction of water-saving technologies, the improvement of water accounting and monitoring, and the formation of an ecological culture. Monitoring results obtained from experimental fields a 44 percent reduction in water consumption, a 50 percent reduction in labor costs, and a 31 percent increase in productivity clearly confirm the project's economic effectiveness. The article further analyses advanced international experiences from Turkey, China, and Spain, as well as mechanisms for enhancing the organizational capacity of WCAs and promoting efficient water use through public-private partnership, digital technologies, and training programs. In conclusion, it is scientifically substantiated that the integrated model of WCAs and the “Water Workers’ School” represents an effective instrument for strengthening participatory water governance and achieving sustainable development under conditions of water scarcity and climate change.